THE GOOD, THE BAD, AND THE UGLY: WOMEN CANDIDACIES AND POLITICAL DYNASTIES IN INDONESIA’S ELECTIONS - Rahmatunnisa, Mudiyati (Universitas Padjadjaran, 2024)
This study investigates the intricate correlation between women’s nominations for political office and the existence of political dynasties in the context of Indonesia’s elections following the downfall of the authoritarian regime. The study specifically examines the complex factors that influence the experiences of women who pursue political positions in a setting where entrenched family legacies hold significant influence. The study employs qualitative methodology with a theory-driven approach. To construct arguments and address the inquiries presented, the author employs secondary sources of information. A multitude of books and recent, authoritative, and pertinent scientific journal articles were utilized as the primary sources of data. This study finds that amidst a significant increase in the number of women running for political offices, the presence of enduring political dynasties adds a complex and nuanced dimension to this evolving journey. Political dynasties provide better access for women with established networks, financial resources, and family influence to pursue political contestation and hence, increase the number of women in elected office. However, the patriarchal nature of many political dynasties in Indonesia frequently results in the marginalization of women, resulting in gender bias and limited decision-making authority. In addition, non-dynastic women candidates are discouraged from participating in the electoral process. The study also argues that women dynastic politics also committed corruption which could undermine the efforts of strengthening women’s political representation This study highlights the need for a balanced perspective on the intersection between women’s candidacies and political dynasties.